1990
DOI: 10.1039/p19900001228
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (–)-probetaenone I: structural confirmation of biosynthetic precursor of betaenone B

Abstract: Probetaenone I (1) has been synthesized by an intramolecular Diels-Alder reaction and, thereby, its structure has been clearly confirmed; in the biosynthesis of betaenone B (2) the stereochemistry of the C-8 hydroxylation of (1) was proved to involve retention of configuration.Paper 9/05458H

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…[26] Synthesis of 47 through an intramolecular Diels-Alder reaction confirmed the structure and provided credence for the proposed biosynthetic pathway. [27] Scheme 8. Incorporation of deuterated trienes into solanapyrones A (26) and D (27).…”
Section: Nargenicinmentioning
confidence: 99%
See 3 more Smart Citations
“…[26] Synthesis of 47 through an intramolecular Diels-Alder reaction confirmed the structure and provided credence for the proposed biosynthetic pathway. [27] Scheme 8. Incorporation of deuterated trienes into solanapyrones A (26) and D (27).…”
Section: Nargenicinmentioning
confidence: 99%
“…[27] Scheme 8. Incorporation of deuterated trienes into solanapyrones A (26) and D (27). The thioacetal of 27 is the major product (2:1) in the laboratory synthesis.…”
Section: Nargenicinmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 In 2015, we identified a betaenone octaketide synthase (Bet1) and a trans-acting enoyl reductase (Bet3), which participate in the formation of dehydroprobetaenone I (5) having a decalin scaffold by heterologous expression of the corresponding genes (Scheme 3). 21 Chemical reactivity and conformational analysis suggested that involvement of DAase PKS Bet1 at the stage of reductive release of growing polyketide chain giving reactive trienone although non-enzymatic reaction 22 cannot be ruled out.…”
Section: Intramolecular Daases Generating Decalin Skeletonsmentioning
confidence: 99%